Legal Protection of the Right to a Healthy Environment from Waste Pollution in Indonesia - Yuninda Dwi Kartika; Heddy Permana Putra; Asep Kustiwa; Alam Abdurrahman; Sungguh Raja Sembiring (Civiliza Publishing, 2026)
Waste that is not managed in an environmentally sound manner has become a major source of secondary pollution in Indonesia, affecting soil, water, air quality, public health, and the enjoyment of constitutional environmental rights. This study examines the positive-law framework protecting the public right to a good and healthy environment from waste pollution and evaluates the effectiveness of preventive and repressive legal instruments available to affected communities. The research uses normative legal research with statutory and conceptual approaches. Primary legal materials include the 1945 Constitution, Law No. 32 of 2009 on Environmental Protection and Management, and Law No. 18 of 2008 on Waste Management; secondary materials consist of environmental law scholarship and official institutional reports. The study finds that Indonesian law provides a layered architecture of protection through constitutional environmental rights, environmental approvals, strategic environmental assessment, public participation, administrative sanctions, civil remedies, criminal enforcement, class actions, and Anti-SLAPP protection. Nevertheless, enforcement remains constrained by weak local oversight, conventional end-of-pipe waste governance, high litigation costs, and scientific difficulties in proving causation. The article argues that civil environmental protection should be strengthened through effective application of strict liability and evidentiary mechanisms that reduce the disproportionate burden borne by pollution victims. Such an approach is necessary to improve access to justice and advance environmental justice for communities exposed to waste pollution.